Pharmacy and medicine in Ancient Egypt : proceedings of the conference held in Barcelona (2018) - Dinarès Solà, Rosa,; Fernandez Georges, Mikel,; Guasch Jané, Maria Rosa, (Archaeopress Egyptology ;, 2021)
This volume presents the proceedings of the 3rd International Conference on Pharmacy and Medicine in Ancient Egypt (Barcelona, October 2018) showcasing the most recent pharmaceutical and medical studies on human remains and organic and plant material from ancient Egypt, together with discussions on textual and iconographical evidence.